Lentiviral-mediated expression of cytochrome P450 2D6 in HepaRG cells: new means for in vitro xenobiotic biotransformation and cellular response to chimeric viral mRNA - Hugo Coppens-Exandier; Franz Mackanga; Thomas Darde; Corentin Bonhomme; Gaëlle Angenard; Patricia Leroyer; Catherine Ribault; Thomas Gicquel; Romain Pelletier; Flyuza Roshchina; Estelle Schaefer; Christophe Chesné; et al. (Archives of Toxicology, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

The carbon dioxide radical anion as a reductant in water treatment and atmospheric chemistry: a review - Thomas Schaefer; Jonathan D. Raff; Mallikarjuna N. Nadagouda; Eric Lichtfouse; Dan Meyerstein; Hartmut Herrmann; Virender K. Sharma (Environmental Chemistry Letters, 2026)
The carbon dioxide radical anion, CO 2 ●− , is a highly reactive radical species involved in the reduction of the CO 2 greenhouse gas, organic synthesis, atmospheric aerosol chemistry, and treatment of halogenated compounds. In recent years, CO 2 ●− has emerged as a strong reductant, or single electron donor. Here we present techniques used to generate CO 2 ●− and we discuss applications to degrading pollutants such as halogenated alkanes. The potential occurrence of such reductions in water and aqueous aerosols is discussed, notably for the degradation of perfluoroalkyl substances. In the laboratory, CO 2 ●− is directly generated by either direct electrochemical reduction of CO 2 or hydrogen atom transfer of either formate salts with and without catalysts or ferrioxalate through photochemical or radiolytic processes. The CO 2 ●− has an ultraviolet spectrum, and CO 2 ●− vibration modes are characterized by fast kinetics using infrared and Raman spectroscopy. The second-order rate constants of the reactions of CO 2 ●− with halogenated alkanes, of -1.84 ± 0.22 V, are generally slower than that of the hydrated electron, of -2.87 V, and give a negative linear relationship with energy of lower unoccupied molecular orbital, suggesting single electron transfer mechanism in reducing the halogenated compounds.

Simulated atmospheric transformation of the tire additives in the aqueous phase: 6-PPD, 6-PPD quinone, diphenylguanidine, and dicyclohexylamine - Volkwin Kuntz; Natalie Kamprad; Bettina Seiwert; Thomas Schaefer; Hartmut Herrmann; Thorsten Reemtsma; Daniel Zahn (Environmental Pollution, 2026)

Rapid thinning of the Cordillera Darwin Icefield at the onset of Termination I - B.L. Hall; A.E. Putnam; T.V. Lowell; G.H. Denton; J.L. Russell; R.L. Soteres; M.M. Spoth-Ascencao; M.L. Miles; S.G. Thomas; P.I. Moreno; R. Schwartz; J.M. Schaefer (Quaternary Science Reviews, 2026)

HESI GTTC ring trial: Concordance between Ames and rodent carcinogenicity outcomes for N-nitrosamines (NAs) with rat and hamster metabolic conditions - Joel Bercu; Alejandra Trejo-Martin; Connie Chen; Maik Schuler; Jennifer Cheung; Tetyana Cheairs; Anthony M. Lynch; Dean Thomas; Andreas Czich; Aisar Atrakchi; Timothy J. McGovern; Robert H. Heflich; et al. (Regulatory Toxicology and Pharmacology, 2025)

Multi-element isotope fractionation analysis to investigate the photosensitized reactions of humic substance with 3-chloroaniline - Ning Min; Jun Yao; Hao Li; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Herrmann Richnow (Water Research, 2025)

Leaky pollination barrier in edaphic vicarious alpine plants - Thomas Huber; Roman Fuchs; Julian Robin; Andreas Tribsch; Stefan Dötterl; Hanno Schaefer (Arthropod-Plant Interactions, 2025)
Adaptation to siliceous versus carbonate substrates is thought to be an important driver of speciation in the alpine flora. The role of the pollination system in the formation and maintenance of such species is presently unclear. Here, we chose three species pairs in the genera Gentiana , Primula , and Rhododendron which often occur in geographic proximity or even sympatry to study the existence of pollination barriers in these lineages. Using remote camera and direct observation approaches, scent and color analyses, we tested the hypothesis whether divergent pollinator communities exist that could help to maintain genetic separation of plant populations adapted to different soil types. We found differences in frequency, diurnal activity and to some extent also community composition of flower visitors in edaphic vicarious species pairs. Floral traits like color and scent as well as flower visitor co-distributions indicate that our study species have divergent but overlapping pollination systems. Our results do not suggest a strong reproductive barrier function of the pollination system. While adaptation to different soils still seems to be the main force keeping edaphic vicarious alpine plants genetically separated, pollinators might mediate hybridization in contact areas.

Multi-element compound-specific stable isotope analysis (2H, 13C, 15N, 33/34S) to characterize the mechanism of sulfate and hydroxyl radical reaction and photolysis of benzothiazole - Haiyan Yu; Limin Ma; Steffen Kümmel; Xiao Liu; Thomas Schaefer; Hartmut Herrmann; Hans-Hermann Richnow (Water Research, 2025)

Carbon, hydrogen, nitrogen and chlorine isotope fractionation during 3-chloroaniline transformation in aqueous environments by direct photolysis, TiO2 photocatalysis and hydrolysis - Ning Min; Jun Yao; Hao Li; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genomic evidence for the widespread presence of GH45 cellulases among soil invertebrates - Hannah Muelbaier; Freya Arthen; Gemma Collins; Thomas Hickler; Karin Hohberg; Ricarda Lehmitz; Yannick Pauchet; Markus Pfenninger; Anton Potapov; Juliane Romahn; Ina Schaefer; Stefan Scheu; et al. (Molecular Ecology, 2024)
Lignocellulose is a major component of vascular plant biomass. Its decomposition is crucial for the terrestrial carbon cycle. Microorganisms are considered primary decomposers, but evidence increases that some invertebrates may also decompose lignocellulose. We investigated the taxonomic distribution and evolutionary origins of GH45 hydrolases, important enzymes for the decomposition of cellulose and hemicellulose, in a collection of soil invertebrate genomes. We found that these genes are common in springtails and oribatid mites. Phylogenetic analysis revealed that cellulase genes were acquired early in the evolutionary history of these groups. Domain architectures and predicted 3D enzyme structures indicate that these cellulases are functional. Patterns of presence and absence of these genes across different lineages prompt further investigation into their evolutionary and ecological benefits. The ubiquity of cellulase genes suggests that soil invertebrates may play a role in lignocellulose decomposition, independently or in synergy with microorganisms. Understanding the ecological and evolutionary implications might be crucial for understanding soil food webs and the carbon cycle.

Carbon and hydrogen isotope fractionation of phthalates during photocatalysis reactions in aqueous solution containing Fe(III) complexes or iron minerals - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Oliver J. Lechtenfeld; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2023)

Carbon isotope fractionation of di-(2-ethylhexyl)-phthalate during photosensitized degradation by •OH and S O 4 · - for characterization of reaction mechanisms - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Chemical Engineering Journal, 2023)

Aqueous-phase photo-oxidation of selected green leaf volatiles initiated by OH radicals: Products and atmospheric implications - Kumar Sarang; Tobias Otto; Sahir Gagan; Krzysztof Rudzinski; Thomas Schaefer; Martin Brüggemann; Irena Grgić; Adam Kubas; Hartmut Herrmann; Rafal Szmigielski (Science of The Total Environment, 2023)

Assessing variants of uncertain significance implicated in hearing loss using a comprehensive deafness proteome - Mallory R. Tollefson; Rose A. Gogal; A. Monique Weaver; Amanda M. Schaefer; Robert J. Marini; Hela Azaiez; Diana L. Kolbe; Donghong Wang; Amy E. Weaver; Thomas L. Casavant; Terry A. Braun; Richard J. H. Smith; et al. (Human Genetics, 2023)
Hearing loss is the leading sensory deficit, affecting ~ 5% of the population. It exhibits remarkable heterogeneity across 223 genes with 6328 pathogenic missense variants, making deafness-specific expertise a prerequisite for ascribing phenotypic consequences to genetic variants. Deafness-implicated variants are curated in the Deafness Variation Database (DVD) after classification by a genetic hearing loss expert panel and thorough informatics pipeline. However, seventy percent of the 128,167 missense variants in the DVD are “variants of uncertain significance” (VUS) due to insufficient evidence for classification. Here, we use the deep learning protein prediction algorithm, AlphaFold2, to curate structures for all DVD genes. We refine these structures with global optimization and the AMOEBA force field and use DDGun3D to predict folding free energy differences (∆∆G Fold ) for all DVD missense variants. We find that 5772 VUSs have a large, destabilizing ∆∆G Fold that is consistent with pathogenic variants. When also filtered for CADD scores (> 25.7), we determine 3456 VUSs are likely pathogenic at a probability of 99.0%. Of the 224 genes in the DVD, 166 genes (74%) exhibit one or more missense variants predicted to cause a pathogenic change in protein folding stability. The VUSs prioritized here affect 119 patients (~ 3% of cases) sequenced by the OtoSCOPE targeted panel. Approximately half of these patients previously received an inconclusive report, and reclassification of these VUSs as pathogenic provides a new genetic diagnosis for six patients.

New perspectives on soil animal trophic ecology through the lens of C and N stable isotope ratios of oribatid mites - Mark Maraun; Tanja Thomas; Elisabeth Fast; Nico Treibert; Tancredi Caruso; Ina Schaefer; Jing-Zhong Lu; Stefan Scheu (Soil Biology and Biochemistry, 2023)

Barium isotope composition of depleted MORB mantle constrained by basalts from the South Mid-Atlantic Ridge (5–11°S) with implication for recycled components in the convecting upper mantle - Fei Wu; Simon Turner; Kaj Hoernle; Folkmar Hauff; Bruce F. Schaefer; Thomas Kokfelt; Ilya Bindeman (Geochimica et Cosmochimica Acta, 2023)

Porosity, strength, and alteration – Towards a new volcano stability assessment tool using VNIR-SWIR reflectance spectroscopy - Gabor Kereszturi; Michael Heap; Lauren N. Schaefer; Herlan Darmawan; Frances M. Deegan; Ben Kennedy; Jean-Christophe Komorowski; Stuart Mead; Marina Rosas-Carbajal; Amy Ryan; Valentin R. Troll; Marlène Villeneuve; et al. (Earth and Planetary Science Letters, 2023)

AudioGene: refining the natural history of KCNQ4, GSDME, WFS1, and COCH-associated hearing loss - Ryan K. Thorpe; W. Daniel Walls; Rae Corrigan; Amanda Schaefer; Kai Wang; Patrick Huygen; Thomas L. Casavant; Richard J. H. Smith (Human Genetics, 2022)

MYT1L-associated neurodevelopmental disorder: description of 40 new cases and literature review of clinical and molecular aspects - Juliette Coursimault; Anne-Marie Guerrot; Michelle M. Morrow; Catherine Schramm; Francisca Millan Zamora; Anita Shanmugham; Shuxi Liu; Fanggeng Zou; Frédéric Bilan; Gwenaël Le Guyader; Ange-Line Bruel; Anne-Sophie Denommé-Pichon; et al. (Human Genetics, 2022)

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

A comparative analysis of genetic hearing loss phenotypes in European/American and Japanese populations - W. Daniel Walls; Hideaki Moteki; Taylor R. Thomas; Shin-ya Nishio; Hidekane Yoshimura; Yoichiro Iwasa; Kathy L. Frees; Carla J. Nishimura; Hela Azaiez; Kevin T. Booth; Robert J. Marini; Diana L. Kolbe; et al. (Human Genetics, 2020)

Pyridyl-Ala Modified Cyclic Hexapeptides: In-Vitro and In-Vivo Profiling for Oral Bioavailability - Thomas Vorherr; Ian Lewis; Joerg Berghausen; Felix Huth; Michael Schaefer; Roman Wille; Jinhai Gao; Bing Wang (International Journal of Peptide Research and Therapeutics, 2020)
We and others have been aiming at modifications to maintain or to enhance solubility while enabling permeability for cyclic hexapeptides. Especially, the 2-pyridyl-Ala modification was investigated, since in this case, the pyridyl-nitrogen is able to form an H-bond to the NH of the same residue. The hypothesis of a backbone side-chain interaction was demonstrated by NMR experiments, and further results obtained on a variety of pyridyl-Ala derivatives, studied systematically in the context of permeability, are presented in this contribution. Thus, this study sheds some more light on the pyridyl-Ala modification, which had been reported earlier. In addition to the in vitro profiling, the extent of oral bioavailability was assessed in rats. In principle, the pyridyl-Ala residue can be considered as an amino acid supporting oral uptake. Graphic Abstract

Genomic sequencing of a virus representing a novel type within the species Dyopipapillomavirus 1 in an Indian River Lagoon bottlenose dolphin - Galaxia Cortés-Hinojosa; Kuttichantran Subramaniam; James F. X. Wellehan; Terry Fei Fan Ng; Eric Delwart; Stephen D. McCulloch; Juli D. Goldstein; Adam M. Schaefer; Patricia A. Fair; John S. Reif; Gregory D. Bossart; Thomas B. Waltzek (Archives of Virology, 2019)

Deglaciation of coastal south‐western Spitsbergen dated with in situ cosmogenic 10 Be and 14 C measurements - Nicolás E. Young; Jennifer Lamp; Toby Koffman; Jason P. Briner; Joerg Schaefer; Endre F. Gjermundsen; Henriette Linge; Susan Zimmerman; Thomas P. Guilderson; Derek Fabel; Anne Hormes (Journal of Quaternary Science, 2018)
The Svalbard–Barents ice sheet was predominantly a marine‐based ice sheet and reconstructing the timing and rate of its decay during the last deglaciation informs predictions of future decay of marine‐based ice sheets (e.g. West Antarctica). Records of ice‐sheet change are routinely built with cosmogenic surface exposure ages, but in some regions, this method is complicated by the presence of isotopic inheritance yielding artificially old and erroneous exposure ages for the most recent deglaciation. We present 46 10 Be ages from south‐western Spitsbergen that, when paired with in situ 14 C measurements ( n = 5), constrain the timing of coastal deglaciation following the last glacial maximum. 10 Be and in situ 14 C measurements from bedrock along a ∼400‐m elevation transect reveal inheritance‐skewed 10 Be ages, whereas in situ 14 C measurements constrain 400 m of ice‐sheet thinning and coastal deglaciation at 17.4 ± 1.5 ka. Our in situ 14 C‐dated transect, combined with three additional 10 Be‐dated coastal sites, show that the south‐western margin of the Svalbard–Barents ice sheet retreated out of the Norwegian Sea between ∼18 and 16 ka. In situ 14 C measurements provide key chronological information on ice‐sheet response to the last termination in cases where measurements of long‐lived nuclides are compromised by isotopic inheritance.

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Modulation of Oral Bioavailability and Metabolism for Closely Related Cyclic Hexapeptides - Thomas Vorherr; Ian Lewis; Joerg Berghausen; Sandrine Desrayaud; Michael Schaefer (International Journal of Peptide Research and Therapeutics, 2018)

Emergent climate and CO 2 sensitivities of net primary productivity in ecosystem models do not agree with empirical data in temperate forests of eastern North America - Christine R. Rollinson; Yao Liu; Ann Raiho; David J. P. Moore; Jason McLachlan; Daniel A. Bishop; Alex Dye; Jaclyn H. Matthes; Amy Hessl; Thomas Hickler; Neil Pederson; Benjamin Poulter; et al. (Global Change Biology, 2017)
Ecosystem models show divergent responses of the terrestrial carbon cycle to global change over the next century. Individual model evaluation and multimodel comparisons with data have largely focused on individual processes at subannual to decadal scales. Thus far, data‐based evaluations of emergent ecosystem responses to climate and CO 2 at multidecadal and centennial timescales have been rare. We compared the sensitivity of net primary productivity ( NPP ) to temperature, precipitation, and CO 2 in ten ecosystem models with the sensitivities found in tree‐ring reconstructions of NPP and raw ring‐width series at six temperate forest sites. These model‐data comparisons were evaluated at three temporal extents to determine whether the rapid, directional changes in temperature and CO 2 in the recent past skew our observed responses to multiple drivers of change. All models tested here were more sensitive to low growing season precipitation than tree‐ring NPP and ring widths in the past 30 years, although some model precipitation responses were more consistent with tree rings when evaluated over a full century. Similarly, all models had negative or no response to warm‐growing season temperatures, while tree‐ring data showed consistently positive effects of temperature. Although precipitation responses were least consistent among models, differences among models to CO 2 drive divergence and ensemble uncertainty in relative change in NPP over the past century. Changes in forest composition within models had no effect on climate or CO 2 sensitivity. Fire in model simulations reduced model sensitivity to climate and CO 2 , but only over the course of multiple centuries. Formal evaluation of emergent model behavior at multidecadal and multicentennial timescales is essential to reconciling model projections with observed ecosystem responses to past climate change. Future evaluation should focus on improved representation of disturbance and biomass change as well as the feedbacks with moisture balance and CO 2 in individual models.

A Detailed Investigation on Conformation, Permeability and PK Properties of Two Related Cyclohexapeptides - Ian Lewis; Michael Schaefer; Trixie Wagner; Lukas Oberer; Emine Sager; Peter Wipfli; Thomas Vorherr (International Journal of Peptide Research and Therapeutics, 2015)

An integrated field-numerical approach to assess slope stability hazards at volcanoes: the example of Pacaya, Guatemala - Lauren N. Schaefer; Thomas Oommen; Claudia Corazzato; Alessandro Tibaldi; Rudiger Escobar-Wolf; William I. Rose (Bulletin of Volcanology, 2013)

Dating of raised marine and lacustrine deposits in east Greenland using beryllium‐10 depth profiles and implications for estimates of subglacial erosion - Brent M. Goehring; Meredith A. Kelly; Joerg M. Schaefer; Robert C. Finkel; Thomas V. Lowell (Journal of Quaternary Science, 2010)
Here we combine 10 Be depth profile techniques applied to late glacial ice‐contact marine and lacustrine deltas, as well as boulder exposure dating of associated features in the Scoresby Sound region, east Greenland, to determine both the surface age and the magnitude of cosmogenic nuclide inheritance. Boulder ages from an ice‐contact delta in northern Scoresby Sund show scatter typical of polar regions and yield an average age of 12.8 ± 0.5 ka – about 2 ka older than both our average profile surface age of 10.9 ± 0.7 ka from three depth profiles and a radiocarbon‐based estimate. On the other hand, boulder exposure ages from a set of moraines in southern Scoresby Sund show excellent internal consistency for polar regions and yield an average age of 11.6 ± 0.2 ka. The profile surface age from a corresponding ice‐contact delta is 8.1 ± 0.9 ka, while a second delta yields an age of 10.0 ± 0.4 ka. Measured 10 Be inheritance concentrations from all depth profiles are internally consistent and are between 10% and 20% of the surface concentrations, suggesting a regional cosmogenic inheritance signal for the Scoresby Sound landscape. Based on the profile inheritance concentrations, we explore the first‐order catchment‐averaged bedrock erosion under the Greenland ice sheet, yielding estimates of total erosion during the last glacial cycle of the order of 2–30 m. Copyright © 2010 John Wiley & Sons, Ltd.

Comparison of SLCO1B1 sequence variability among German, Turkish, and African populations - Jessica Mwinyi; Karla Köpke; Melanie Schaefer; Ivar Roots; Thomas Gerloff (European Journal of Clinical Pharmacology, 2008)

Influence of the SLCO1B1*1b and *5 haplotypes on pravastatin’s cholesterol lowering capabilities and basal sterol serum levels - Thomas Gerloff; Melanie Schaefer; Jessica Mwinyi; Andreas Johne; Thomas Sudhop; Dieter Lütjohann; Ivar Roots; Klaus von Bergmann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

Reproductive responses of two related coexisting songbird species to environmental changes: global warming, competition, and population sizes - Thomas Schaefer; Gösta Ledebur; Josef Beier; Bernd Leisler (Journal of Ornithology, 2006)

Transient receptor potential channels as molecular substrates of receptor-mediated cation entry - Thomas Hofmann; Michael Schaefer; Günter Schultz; Thomas Gudermann (Journal of Molecular Medicine, 2000)

Transient receptor potential channels as molecular substrates of receptor-mediated cation entry - Thomas Hofmann; Michael Schaefer; Günter Schultz; Thomas Gudermann (Journal of Molecular Medicine, 2000)

Bioequivalence of Topical Dermatological Dosage Forms-Methods of Evaluation of Bioequivalence - Vinod P. Shah; Gordon L. Flynn; Avraham Yacobi; Howard I. Maibach; Charles Bon; Nicholas M. Fleischer; Thomas J. Franz; Stanley A. Kaplan; Jeff Kawamoto; Lawrence J. Lesko; Jean-Paul Marty; Lynn K. Pershing; et al. (Pharmaceutical Research, 1998)